Implementation of BIM Using the Tekla Application in the Permata River View Housing Development Project - Ananda Mixola Tampubolon; Sari, Yusra Aulia (Journal of Civil Engineering and Planning (JCEP), 2024)
With increasing development in the construction sector, construction implementers are required to be faster and more efficient in completing project activities. The Permata River View housing development does not use BIM in its implementation. This research aims to carry out modeling with BIM software in 3D form and Quantity take-off. In this research, the Tekla Structures application will be used in the Permata River View housing complex. The modeling will start from the foundation, sloof, beams and columns along with the reinforcement. In this modeling, the material standards and concrete compressive strength are adjusted to SNI, the distribution of reinforcement in the Permata River View housing complex does not comply with the SRPKM and SRPMM stated in the SNI 2847:2019 regulations. However, the distribution of reinforcement is still in accordance with SNI. In this modeling we also get a comparison from Tekla Structures to RAB of 94.25% for concrete and 115.1% for reinforcement. The application of BIM using the Tekla Structures Application produces more accurate calculations and also makes work easier so it is faster, saves human resources and also and can be accounted for with objects that have been modeled in Tekla Structures